2012
DOI: 10.1524/ract.2012.1948
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of Np(V/VI) redox speciation in hyperalkaline TMA-(OH, Cl) solutions

Abstract: Neptunium(V/VI) / TMA-OH / XANES reference spectra / EXAFSSummary. The redox chemistry of Np(V/VI) was investigated in ∼ 0.6 M tetramethylammonium hydroxide/chloride (TMA-(OH, Cl)) solutions with 9 ≤ − log[H + ] ≤ 13.5. Redox conditions were defined by the absence or presence of ClO − as oxidizing agent (Na-salt, 5 × 10 These results indicate that Np(VI) aqueous species and solid compounds prevail far below the oxidation border of water in alkaline solutions and also far below the E H border calculated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
23
1
1
Order By: Relevance
“…Figure 5 shows the XANES spectra of the solid phases described in Table 1. The comparison of these spectra with Np(IV), Np(V) and Np(VI) reference spectra reported elsewhere [67] clearly indicates that neptunium is predominantly found as +V in all solid phases characterized in this study.…”
Section: Aqueous Speciation By Uv-vis/nirsupporting
confidence: 77%
See 2 more Smart Citations
“…Figure 5 shows the XANES spectra of the solid phases described in Table 1. The comparison of these spectra with Np(IV), Np(V) and Np(VI) reference spectra reported elsewhere [67] clearly indicates that neptunium is predominantly found as +V in all solid phases characterized in this study.…”
Section: Aqueous Speciation By Uv-vis/nirsupporting
confidence: 77%
“…The distance determined for Np-O eq is in average longer than the distance recently reported for freshly precipitated NpO 2 OH(am) in TMA-OH solutions (2.35 ± 0.03 Å) [67]. Cu Kα radiation NaNpO 2 (OH) 2 (cr) -Almond et al [37] Figure 3: XRD spectra of selected solid phases from Np(V) solubility experiments in 0.1, 1.0, 3.0 and 5.0 M NaCl (m NaCl = 0.10, 1.02, 3.20 and 5.61 m).…”
Section: Xanes and Exafscontrasting
confidence: 59%
See 1 more Smart Citation
“…However, the possible formation of anionic Np(VI) species (NpO 2 (OH) 3 − and NpO 2 (OH) 4 2− ) under oxidizing alkaline conditions, in analogy to U(VI), may significantly limit the stability field of Np(V) in favour of Np(VI) species. Recently, Np redox speciation studies have confirmed the analogy between the uranium and neptunium speciation under alkaline, oxidizing conditions [5]. A predominance diagramme for Np in the pH range 10 < pH < 14 including the anionic Np(VI) species (NpO 2 (OH) 3 − and NpO 2 (OH) 4 2− ), shows that all three redox states may occur under the redox conditions expected in a L/ILW repository (gray-coloured regions in Figure 1a).…”
Section: Introductionmentioning
confidence: 88%
“…Titanium dioxide (TiO 2 ) is a solid phase known to be stable under alkaline conditions and ambient temperature with low solubility and slow recrystallization [4]. Therefore, radionuclide incorporation into the , d) calculated using the NEA thermodynamic database [9] completed with stability constants for the hexavalent NpO 2 (OH) 2 (aq) [5], NpO 2 (OH) 3 − and NpO 2 (OH) gray-coloured fields in the predominance diagram represent the redox potential ranges expected in the cementitious near-field of a L/ILW repository [11,12].…”
Section: Introductionmentioning
confidence: 99%